Potensi Bahaya Kerja Pada Pekerja Di Pabrik Tahu Kelurahan Tonja-Denpasar - Negara, Ni Luh Gede Aris Maytadewi; Haryawan, I.G.A; Prihastini, K.A; Biomi, A.A; Dharmayanti, C.I (STIKES Yayasan RS.Dr.Soetomo, 2023)
The informal sector has characteristics such as small-scale business, individual ownership, simple technology, low level of education, and skills of workers: low productivity and relatively low wages. One of the informal sector businesses is the home-based tofu industry. In general, workers at the tofu manufacturing site have not received health insurance and safety guarantees if they suffer from occupational diseases or work accidents. In the process itself, there are many potential occupational hazards that may affect the health level of workers, so it is deemed necessary to socialize potential occupational hazards to workers in the tofu factory. The purpose of this activity is to provide information to informal sector workers, especially workers in factories, to know about the potential work hazards that may occur during work so that they can protect themselves from accidents or occupational diseases. The method used is socialization with workers, followed by discussions to assess workers' understanding of potential hazards during work. Workers understand the potential hazards that may occur in their work environment, so they can protect themselves from accidents or occupational diseases. The socialization of potential occupational hazards to workers in tofu factories as an effort to pay attention to workers in the informal sector has been achieved, so it is hoped that the health and safety of workers is guaranteed